Improving the Understanding of Fishing Communities in Cikiruhwetan Village-Pandeglang Regency Through Capture Fisheries Training Activities - Novita, Yopi; Wisudo, Sugeng Hari; Iskandar, Budhi Hascaryo; Mawardi, Wazir; Kurniawati, Vita Rumanti; Yuwandana, Dwi Putra (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2024)
The Ministry of Marine Affairs and Fisheries (KKP) has designated several fishing villages throughout Indonesia as kalaju villages, one of which is Cikiruhwetan Village, Pandeglang Regency, Banten Province. However, the development of kalaju village in Cikiruhwetan Village has not been optimized, so there is no visible difference between kalaju village and non-kalaju village. Therefore, in order to optimize the development of kalaju village, the village community needs to be equipped with various understandings that can improve their abilities, especially abilities in the field of capture fisheries. The improvement of understanding is carried out in the form of training or technical guidance involving the fishing community and agency employees and village officials. Changes or improvements in understanding were tested using written questions given at the beginning of the training (pre-test) and at the end of the training (post-test). Based on the evaluation results of the pre-test and post-test results, it can be seen that there is an increase in the understanding of the fishing community on the material provided. Although the increase in understanding has not been optimal, it can be done through regular training.